Pengaruh Bahan Setek dan Pemberian ZPT NAA Terhadap Pertumbuhan Bibit Tanaman Buah Naga Merah (Hylocereus costaricensis (Web) Britton & Rose) - Lisanul Fahmi Sihombing; Rosita Sipayung; Meiriani Meiriani (Jurnal Agroekoteknologi, 2017)
Red dragon fruit is a commodity with high economic value and it provides many benefits. However the supply of seeds that are less optimal causes high price. The use of cutting material and the provision of planting cuttings of growth regulators sought to increase the production of dragon fruit. The experiment was conducted in in the field of research Faculty of Agriculture, University of North Sumatra, on February to April 2016, using a factorial randomized block design with two factors, the first factor ispart of the stem cuttings (Bottom, middle, top) and the second factor is concentration of NAA (0, 100, 200, 300, 400, 500 ppm). Observed were increase sprouting age, the number of shoots, The sprouting of percentage, The average of shoot length, The rooting of percentage, volume of root, root wet weight, root dry weight. The results showed that application of part of the stem cuttings increasedThe number of shoots and root dry weight.The giving plant growth increased the sprouting age,the sprouting of percentage, the number of shoots,the average of shoot length , and root dry weight. andthe interaction increased theroot dry weight. Keywords: cuttings, NAA, red dragon fruit  Abstrak Buah naga merah merupakan komoditas yang bernilai ekonomi tinggi dan banyak memberikan manfaat. Namun penyediaan bibit yang kurang optimal menyebabkan harga jual yang tinggi. Penggunaan bahan tanam setek dan pemberian zat pengatur tumbuh diupayakan dapat meningkatkan produksi buah naga.Penelitian dilaksanakan dilahan penelitian Fakultas Pertanian,Univeristas Sumatera Utara,pada bulan Februari sampai April 2016,menggunakan Rancangan Acak Kelompok Faktorial dengan dua faktor yaitu Bahan Setek (Bawah, Tengah, Ujung) dan Konsentrasi NAA (0, 100, 200, 300, 400, 500 ppm). Peubah yang diamati adalah umur bertunas, persentase setek bertunas, jumlah tunas, rata-rata panjang tunas, persentase setek berakar, volume akar, bobot basah akar, bobot kering akar. Hasil penelitian menunjukkan bahwa perlakuan bagian batang setek meningkatkan jumlah tunas dan bobot kering akar. Pemberian konsentrasi NAA meningkatkan umur bertunas,persentase setek bertunas,jumlah tunas,panjang tunas dan bobot kering akar. Interaksi keduanya nyata meningkatkan bobot kering akar. Kata kunci : buah naga merah, NAA, setek